Social support network of family members of abused children and adolescents: Perspectives and possibilities. Issue 5 (26th September 2018) - Carlos, Diene Monique; Silva, Lygia Maria Pereira; Beserra, Maria Aparecida; Aragão, Ailton de Souza; Gregory, Alison; Ferriani, Maria das Graças Carvalho
Abstract: Aims and objectives: To analyse the network of care and social support from the perspectives of family members of children and adolescents who have been abused. Background: The theoretical–methodological background of the ecological model for understanding violence and the Paradigm of Complexity provide a broad perspective of violence. The paradigm considers all aspects that constitute a phenomenon as well as particular features. Design: Qualitative research based on the Paradigm of Complexity, developed by Edgar Morin, the primary philosopher. We have adhered to the COREQ Checklist guidelines for qualitative research. Methods: Data were collected through Minimal Maps of Personal Social Networks, and semi‐structured interviews were held with 15 families who were assisted by a nongovernmental organisation in a Brazilian city. The notions of comprehension and contextualisation guided the data analysis. Results: Two categories emerged from the data analyses: "Social isolation" and "Affective relationships needs." The maps revealed a weakened and limited network with low‐density, homogeneous bonds and few significant bonds. Therefore, the network provided predominantly instrumental and material social support with few important effective relationships. The participants disclosed some strategies to empower their lives. Conclusions: We conclude that it is urgent to develop strategies in a broad manner to promote family empowerment, especially on education and employment dimension, and to construct supportive and respectful relationships between services and families as well. Relevance to clinical practice: The present study contributes to international clinical nursing, especially in low‐ and middle‐income countries, by discussing (a) looking at and caring for family members of children and adolescents who have been abused in a contextualised manner; (b) family empowerment, which enables them to have access to healthier environments and to educational/employment opportunities; and (c) broad comprehension of health care among the family members, which provides perspectives not only for looking at violence but also for strengthening supportive social relationships.